Alterations in bone malformation in the absence of the endosomal SNAREs Vti1a and Vti1b - Simone Schmücker; Susanne Schöning; Christiane Wiegand; Sascha Michael Höfling; Christian Bollmann; Judith Koliwer; Gabriele Fischer von Mollard (PLoS ONE, 2026)
The Qb-SNAREs (soluble N-ethylmaleimide-sensitive-factor attachment receptor) Vti1a and Vti1b participate in membrane fusion in the endosomal system of mammalian cells and are partially redundant. While double deficiency of Vti1a -/- Vti1b -/- (DKO) is perinatal lethal, double heterozygous Vti1a +/- Vti1b +/- (DHET) mice presented no phenotypic alterations when compared to wild-type mice. To investigate the physiological role of these proteins, this study focused on the analysis of embryonic DKO versus DHET mice. The size and weight of E18.5 DKO embryos were significantly lower when compared with those of DHET littermates and wild-type embryos. Furthermore, we observed alterations in skeletal development of DKO embryos, mainly in the front limbs, ribs, clavicles and sternum. A lumbar vertebra was missing in DKO embryos and the palate was not closed in 50% of these embryos.